Radiation risk groups of NSC KIPT personnel - Mazilov, A.V.; Stadnik, I.A. (Вопросы атомной науки и техники, 2018)
The characteristics of the NSC KIPT personnel registered on individual dose control in 2017 in terms of the dose matrix are given. The methodologies UNSCEAR-94, BEIR VII, ICRP 2007, currently used to calculate individual radiation risks are described. The main results of calculations of the relative, attributive and absolute radiation risks of personnel for 2017 for various localizations and different groups of radiation risks, banded according to the different methodologies are presented.